Designing a Subsurface Oil and Gas GUI Dashboard Using Design Thinking: Perancangan GUI Dashboard Subsurface Migas dengan Pendekatan Design Thinking - Jannatan, Muhammad Ardhyan; Puspita, Niniek Fajar; Rahardjo, Jani; Harun, Muhammad Rizky (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2025)
Oil and gas companies are currently facing increasingly significant production declines, requiring detailed, accurate and fast subsurface analysis. However, the complexity of large and scattered data, as well as the use of various non-integrated software, are obstacles that cause difficulties and long and inefficient analysis times. Therefore, this study aims to design an intuitive graphical user interface (GUI) dashboard to speed up and facilitate the process as part of the technology management of one of the oil and gas companies in Indonesia. The design thinking and new product development approaches are used to design the system. Qualitative methods are carried out through in-depth interviews, field observations, and surveys to identify user needs and build a subsurface dashboard GUI system, while quantitative methods are used to analyze multi-matrices from the House of Quality (HoQ) and evaluate the intuitiveness and usability of the prototype with the System Usability Scale (SUS) instrument. The analysis was carried out using user personas, customer journey maps, and HoQ to determine the main features. The results of the study indicate that visual graphics, seismic maps and cross-sections, customization, and data management are priority features in the subsurface dashboard GUI system prototype. The SUS evaluation shows that the system is intuitive, user-friendly, and can support work efficiency, as well as suit user needs.